The efficacy and safety of adjunctive perampanel for the treatment of refractory focal‐onset seizures in patients with epilepsy: A meta‐analysis - Yiming Li; Ya Zeng; Jie Mu; Dong Zhou (Epilepsia Open, 2022)
Abstract Objective The last decade has seen an increase in the use of anti‐seizure medications (ASMs); however, the burden of treating drug‐resistant epilepsy has not fallen. We performed this meta‐analysis to evaluate the optimal dose of Perampanel (PER) as a new adjunctive treatment for drug‐resistant seizures. Methods We searched for studies published from inception to February 1, 2021 from PubMed, Central Register of Controlled Trials (CENTRAL), and ScienceDirect. Research characteristics, patients' characteristics, and treatment regimen, concomitant ASMs, clinical outcomes were extracted. The practical outcome included a reduction in seizures frequency ≥50%, ≥75%, and ≥100% from baseline convulsive seizure frequency, and the safety outcome included the proportion of drug withdrawal and adverse reactions. Odds ratios (OR) for 95% confidence intervals (95% CI) were estimated by the inverse variance method. Results Four trials which enrolled 2187 participants (1569 in the PER group and 618 in the placebo group) were included. Results showed that 8 or 12 mg per day had the best effect on all three outcomes, with no significant difference between 8 and 12 mg per day (≥50% reduction, 35.5% vs 36.1%, P = .84; ≥75% reduction, 17.8% vs 19.1%, P = .64; seizure‐free, 3.5% vs 3.7%, P = .85). In addition, 12‐mg PER compared to 8 mg had a higher proportion of trial withdrawal (8.7% vs 17.0%; P < .00001) and treatment‐emergent adverse event (TEAE) resulting in dose reduction/discontinuation (18.5% vs 32.0%; P < .00001). The adverse events (AEs) significantly associated with adjunctive PER were dizziness, somnolence, fatigue, and irritability. Significance Adjunctive treatment of PER was associated with a more significant reduction in the frequency of seizures in patients with refractory epilepsy than placebo, but with a higher frequency of AEs. PER at a daily dose of 8 mg appears to have the best ratio between efficacy and tolerance in most study participants.